2020
DOI: 10.1590/1413-812320202512.16662020
|View full text |Cite
|
Sign up to set email alerts
|

Evolução das publicações em saúde do idoso na Revista Ciência & Saúde Coletiva

Abstract: Resumo O presente trabalho analisou o perfil das publicações relacionadas à saúde do idoso no periódico Ciência & Saúde Coletiva, em termos de sua evolução quantitativa, abordagem metodológica, temática e instituições envolvidas. A seleção dos artigos considerou o título, resumo e descritores e cobriu todo o conteúdo publicado entre 1996 e 2019. Os artigos incluídos foram classificados quanto ao ano de publicação, tipo, temática, abordagem metodológica e vínculo institucional do primeiro autor. A análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
4
0
5
Order By: Relevance
“…In the period 2017 to 2019, there were 867 different authors and the predominant characteristics were similar to those verified in the previous period, with 96.77% Brazilians. Regarding the location of the authors' affiliation institutions, there was a reduction in those located in the Southeast to 39.68% and those in the South to 24.45%, and even so, these two Regions continued to be the highlights with greater participation in the volume of productions, as observed in other studies 7,16 . Nursing education was the most prevalent (29.87%), followed by Physiotherapy (15.46%) and Medicine (13.03%).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In the period 2017 to 2019, there were 867 different authors and the predominant characteristics were similar to those verified in the previous period, with 96.77% Brazilians. Regarding the location of the authors' affiliation institutions, there was a reduction in those located in the Southeast to 39.68% and those in the South to 24.45%, and even so, these two Regions continued to be the highlights with greater participation in the volume of productions, as observed in other studies 7,16 . Nursing education was the most prevalent (29.87%), followed by Physiotherapy (15.46%) and Medicine (13.03%).…”
Section: Resultssupporting
confidence: 70%
“…The linkage of authors to public higher education institutions, for the most part, has been observed in other bibliometric studies, 16,22 and it highlights the social importance of this segment in the scientific production and current reality, as the advancement of science and technology, especially in health, has the potential to promote changes in people's lives and health. Thus, it appears that it is essential that there is encouragement and investment in public education, in disagreement with the funding restrictions that have been observed in Education, science and technology, expanding research groups and increasingly strengthening scientific production on older people health 22 .…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Em 1950, a população idosa representava 4,9% da população do país, já em 2000, esse número passou a representar 7,9%, em 2010 saltou para 10,2% e em 2040 essa porcentagem pode chegar a 23,9%. Desse modo, esse fenômeno causará mudanças no perfil epidemiológico do país, com uma maior incidência de doenças crônicas, desencadeando assim, altos custos para o sistema de saúde (Firmo, 2020).…”
Section: Revisão De Literaturaunclassified